Characterizing inactive ribosomes in translational profiling. Issue 1 (2nd January 2016) - Liu, Botao; Qian, Shu-Bing
ABSTRACT: The broad impact of translational regulation has emerged explosively in the last few years in part due to the technological advance in genome-wide interrogation of gene expression. During mRNA translation, the majority of actively translating ribosomes exist as polysomes in cells with multiple ribosomes loaded on a single transcript. The importance of the monosome, however, has been less appreciated in translational profiling analysis. Here we report that the monosome fraction isolated by sucrose sedimentation contains a large quantity of inactive ribosomes that do not engage on mRNAs to direct translation. We found that the elongation factor eEF2, but not eEF1A, stably resides in these non-translating ribosomes. This unique feature permits direct evaluation of ribosome status under various stress conditions and in the presence of translation inhibitors. Ribosome profiling reveals that the monosome has a similar but not identical pattern of ribosome footprints compared to the polysome. We show that the association of free ribosomal subunits minimally contributes to ribosome occupancy outside of the coding region. Our results not only offer a quantitative method to monitor ribosome availability, but also uncover additional layers of ribosome status needed to be considered in translational profiling analysis.